Biomechanical comparative evaluation of percutaneous fixations with vertebral expansion for vertebral compression fractures: an experimental and finite element study. Issue 5 (4th April 2022) - Lucas, Le Gallo; Lucas, V. P. C. Lima; Sylvain, Persohn; Agathe, Nérot; Marc-Antoine, Rousseau; Laurie, Simon; Wafa, Skalli
Abstract: This study uses in vitro experiments and validated finite element models (FEM) to analyze the effect of posterior fixation, alone or associated with expandable device (ED) and/or cement. 3-dimensional FEMs of intact, fractured and instrumented spine were built and compared with experimental load-displacement curves. FEM ranges of motion were within the experimental corridors. Stresses appeared sensitive to both implant configuration and fracture severity with a stress reduction up to 84%. The FEM highlighted that for a same instrumental strategy, different biomechanical performances were observed according to fracture severity. When bone continuity is altered, both ED and cement may be needed.